Center-Pivot-Irrigated Corn Cost-Return Budget in Western Kansas - Dumler, Troy J.; O'Brien, Daniel M.; Olson, Brian L.S. (My University, 2008)
This publication projects a budget that reflects expected income and costs based on center-pivot-irrigated corn production in western Kansas.
MF585_2008_10
Keywords: MF585; Economics; Crops; MF